Tópicos de física moderna e contemporânea no Ensino Médio: Uma abordagem histórica e conceitual dos modelos atômicos - Melo, José Fernando de (2014)
In the last three decades the research in Physics Education have pointed to the need for the use of Modern and Contemporary Physics (MCP) in High School, as a way to achieve of the Physics’ modernization and renewal contents at this degree of education. However, a few reflections have come to the classroom, and most of the times when they arrive, bring with them the same problems faced like as the previous curriculum, such as complicated mathematical formalism, overburdened workload or lack of appropriate training for teachers. Between these problems, this paper aims to present a didactic proposal to work content (MCP) in High School, using as a support to the science’s history and philosophy. The historical episode studied concerns the development of research into the structure of matter between the late nineteenth and early twentieth century, a period of strong conceptual change in Physics. After a description of didactic proposal, we report the experience of applying it in a class of third year High School students in a school in the city of Campina Grande.